Exploring Volunteer Turnover Reasons, Intentions, and Behavior - Holtrop, Djurre; Soo, C.; Gagné, Marylene; Kragt, D.; Dunlop, Patrick; Luksyte, A. (2024)
Volunteer involving organizations (VIOs) play a vital role in many societies. Yet, turnover among volunteers remains a persistent struggle and VIOs still do not have a good understanding of why volunteers leave. In response, we employed a mixed-methods approach to explore why volunteers consider leaving. By coding textual responses of Australian State Emergency Services and Scouting volunteers (n = 252 and 2235) on an annual engagement survey, we found seven overarching reasons to consider leaving these VIOs: Conflict, high demands and/or low resources, lack of fit, lack of inclusion, personal commitments and circumstances, poor communication and organizational practices, and poor leadership. When contrasted to the reasons that employees leave organizations for, the lack of inclusion and poor communication and organizational practices seem to be uniquely salient reasons that volunteers consider leaving for. Subsequently, guided by the Proximal Withdrawal States theory and using quantitative data from the Scouts sample, we investigated how reasons to consider turnover can predict turnover intentions and turnover behavior. First, volunteers in different withdrawal states cited different potential turnover reasons. For example, volunteers who ‘wanted to stay, but felt they had to leave’ cited personal commitments and circumstances more frequently than those in different withdrawal states. Second, we found that reasons to consider turnover explained little variance in turnover behavior one year later.